Characteristics of consumer trophic resources for Waikato shallow lake food webs - Kevin J. Collier; Jeremy Garrett‐Walker; Deniz Özkundakci; Michael A. Pingram (New Zealand Journal of Marine and Freshwater Research, 2019)
We characterised the quantity (mass per unit area or volume), quality (cabon:nitrogen ratio) and enrichment (δ 15 N) of basal food resources and benthic macroinvertebrates in six shallow lakes in the Waikato region, New Zealand, to elucidate patterns related to lake type (peat, riverine), habitat (littoral, mid‐lake) and enrichment status (Trophic Level Index >6 or ≤5). Total seston dry mass was dominated by fine material that was correlated with chlorophyll a concentration. Seston was a higher quality food resource than benthic particulate organic matter which had higher biomass overall in littoral than in mid‐lake habitats. Biomass of Chironomidae was highest in the less‐enriched peat lakes, possibly due to clearer water supporting benthic algae in shallow littoral areas. Our results highlight the potential role of multiple bottom‐up influences on shallow lake food webs. The more abundant and higher quality pelagic food resources in highly enriched lakes may have implications for resilience to non‐indigenous fish invasion.